“Power Plant Cycle” - Osama Yamin; Abdallah Kmail; Karam Zerie (My University, 2022)
This project aims to describe and give a well-integrated framework for power plant cycle analytic research and conceptual design using all components of Rankine cycle. The main purpose of this project is to generate electric power from many types of fuels and to select the optimal fuel for maximum efficiency. To do so, detailed research and testing on the various types of fuel accessible for usage in the power plant cycle were conducted to create electricity in power plants based on economic logic and effective production. This project includes a wide variety of issues, beginning with an investigation of conventional accessible fuels used in electric power generation, followed by the discovery and use of other fuels. In this project, the main four components (boiler, turbine, pump and condenser) of a Rankine cycle are combined using connecting tools tightly to avoid any leakage thus maintaining the efficiency to obtain all the necessary information to find efficiency theoretically and experimentally in each case of the cycle, so that we can compare the efficiency of many types of fuels. All topics will be discussed in detail and in completion of graduation project 1 to reach the final work and to obtain the final results of this project.